Potassium-sodium niobate-based lead-free ceramic suitable for high-power device and preparation method of potassium-sodium niobate-based lead-free ceramic

By incorporating Bi0.5Na0.5ZrO3 and CuO into potassium niobate ceramics, the phase boundary and defect structure are constructed, and the problems of environmental hazards and performance degradation of lead-based piezoelectric ceramics are solved, and the excellent electrical performance required for high-power electronic equipment is achieved.

CN119638419APending Publication Date: 2025-03-18SICHUAN RAOYU NEW MATERIAL TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411809578.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing lead-based piezoelectric ceramics cause serious harm to the environment, and after improving piezoelectric performance, Curie temperature and quality factors have decreased, making it difficult to achieve commercial application.

Method used

By incorporating Bi0.5Na0.5ZrO3 and CuO into potassium niobate ceramics, the phase boundary and defect structure near room temperature are constructed, and its defect structure and piezoelectric properties are adjusted to achieve comprehensive electrical properties of high voltage electrical coefficient, high quality factors, high Curie temperature and low dielectric loss.

Benefits of technology

It achieves excellent comprehensive electrical properties of potassium niobate-based lead-free ceramics, is suitable for high-power electronic equipment, and is free of lead elements and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638419A_ABST
    Figure CN119638419A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of piezoelectric ceramic materials, in particular to potassium-sodium niobate-based lead-free ceramic suitable for high-power devices and a preparation method, the chemical general formula of the potassium-sodium niobate-based lead-free ceramic is 0.96 (K < 0.45 > Na < 0.55 >) NbO < 3-0.04 > Bi < 0.5 + x > Na < 0.5 > ZrO < 3-0.005 > CuO, and x is one of 0, 0.03, 0.05, 0.08 and 0.10. According to the potassium-sodium niobate-based lead-free ceramic suitable for the high-power device and the preparation method, the potassium-sodium niobate-based lead-free ceramic has excellent comprehensive electrical properties including high piezoelectric constant, high quality factor, high Curie temperature and low dielectric loss, and is suitable for being applied to high-power electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of piezoelectric ceramic materials, and in particular to a potassium sodium niobate-based lead-free ceramic suitable for high-power devices and a preparation method thereof. Background Art

[0002] Piezoelectric ceramics are a new type of functional material that can realize the mutual conversion of mechanical energy and electrical energy. They are widely used in the development of electronic components such as sensors, transducers and buzzers. At present, lead-based piezoelectric ceramics dominate the market, but lead-based piezoelectric ceramics contain a large amount of lead elements, which will cause serious harm to the environment and are not conducive to ecological civilization and sustainable development strategies. Therefore, it is extremely important to explore high-performance lead-free piezoelectric ceramics that can be commercially applied.

[0003] Potassium sodium niobate [(K,Na)NbO3, KNN]-based lead-free ceramics have a high Curie temperature (420oC) and high piezoelectric performance (80pC / N), making them one of the most promising options to replace lead-based piezoelectric ceramics. In recent years, breakthrough work has emerged to optimize the piezoelectric properties of KNN-based ceramics. For example, Wu et al. constructed a new phase boundary by involving components, further refined the ferroelectric domain structure, and improved the piezoelectric performance of KNN-based ceramics to 490-650pC / N. However, with the improvement of piezoelectric performance, its Curie temperature and quality factor have dropped significantly, making it difficult to achieve commercial application.

[0004] With the rapid development of the electronic information industry, the demand for high-power devices is growing, especially lead-free high-power electronic devices, which urgently need in-depth research. For the application of high-power devices, the demand for piezoelectric ceramics is mainly reflected in high piezoelectric coefficient, quality factor, Curie temperature and low dielectric loss. A large number of studies have shown that constructing phase boundaries is the main means to improve piezoelectric performance, and defect structure is the key to achieving high quality factors. Therefore, it has become an urgent task to further develop lead-free piezoelectric materials with high piezoelectric coefficient, high quality factor, high Curie temperature and low dielectric loss through component design and structural optimization. Summary of the invention

[0005] The purpose of the present invention is to provide a potassium sodium niobate-based lead-free ceramic suitable for high-power devices and a preparation method thereof. The potassium sodium niobate-based lead-free ceramic has excellent comprehensive electrical properties, including high piezoelectric constant, high quality factor, high Curie temperature and low dielectric loss, and is suitable for high-power electronic equipment applications.

[0006] To achieve the above object, the present invention provides a potassium sodium niobate-based lead-free ceramic suitable for high-power devices. The chemical formula of the potassium sodium niobate-based lead-free ceramic is 0.96 (K 0.45 Na 0.55 )NbO3-0.04Bi 0.5+xNa 0.5 ZrO3-0.005CuO, wherein x is one of 0, 0.03, 0.05, 0.08 and 0.10.

[0007] The above-mentioned potassium niobate-based lead-free ceramic is prepared by doping Bi into potassium sodium niobate ceramic. 0.5 Na 0.5 ZrO3 is chemically doped to build a phase boundary near room temperature and improve the piezoelectric properties of the ceramic matrix. CuO is added to adjust its defect structure and optimize its quality factor. 0.5+x Na 0.5 ZrO3 treats Bi with excess, which helps to regulate its piezoelectric properties and quality factor while ensuring a high Curie temperature. At the same time, excess Bi helps to increase the density of ceramics and reduce dielectric loss.

[0008] The above-mentioned method for preparing potassium sodium niobate-based lead-free ceramics suitable for high-power devices comprises the following steps:

[0009] S101, weighing raw materials of sodium carbonate, potassium carbonate, niobium pentoxide, bismuth oxide, zirconium oxide and copper oxide according to the molar percentage in the chemical formula of potassium niobate-based lead-free ceramics, adding anhydrous ethanol as a ball milling medium to perform rolling ball milling to obtain a mixed powder;

[0010] S102, drying the mixed powder obtained in S101 to obtain a dry and uniformly mixed mixed powder;

[0011] S103, pre-calcining the mixed powder obtained in S102 at 850° C. for 6 hours to obtain dry powder;

[0012] S104, adding a polyvinyl alcohol aqueous solution to the dry powder obtained in S103, and then sequentially performing granulation, pressing and debinding to obtain a ceramic embryo;

[0013] S105. Sinter the ceramic body obtained in S104 at 1080-1100° C. for 5 hours to obtain lead-free ceramics.

[0014] Preferably, in S101, the ball milling is performed in a ball milling jar, the ball milling jar is a nylon jar, and the grinding balls are zirconium balls.

[0015] Preferably, in S103, pre-firing is performed in a corundum crucible.

[0016] Preferably, in S104, 6 wt % to 8 wt % polyvinyl alcohol aqueous solution is added to the dry powder for granulation to obtain powder particles.

[0017] Preferably, in S104, the pressing is to press the powder particles in an electric tablet press at a pressure of 15 MPa.

[0018] Preferably, electrodes are plated on the lead-free ceramic in S105, and voltage is applied for polarization.

[0019] Preferably, the polarization is performed by polarizing the piezoelectric ceramic body at 3 to 4 kV / cm for 10 to 20 min using a withstand voltage tester.

[0020] Therefore, the present invention adopts the above-mentioned potassium sodium niobate-based lead-free ceramic suitable for high-power devices and the preparation method, and its beneficial effects are:

[0021] 1. Bi of the present invention 0.5 Na 0.5 ZrO3 and CuO can be used to construct phase boundaries and defect structures, respectively. By adding CuO, a large number of defect dipoles are induced to hard-dope the potassium sodium niobate-based lead-free ceramics to improve their quality factors. 0.5+x Na 0.5 ZrO3 is used to prepare Bi element in excess. 3+ With K + and Na + The chemical valence difference between them can adjust the vacancies in the lattice structure, thereby further adjusting its defect structure, thereby synergistically regulating the piezoelectric performance and quality factor while maintaining its high Curie temperature;

[0022] 2. The potassium sodium niobate-based lead-free ceramic provided by the present invention has excellent comprehensive electrical properties, including high piezoelectric constant, high quality factor, high Curie temperature and low dielectric loss, and is suitable for the production and application of high-power electronic equipment in high-cold areas;

[0023] 3. The potassium sodium niobate-based lead-free ceramic provided by the present invention does not contain lead elements, is an environmentally friendly material, and is more beneficial to environmental protection;

[0024] 4. The preparation method provided by the present invention has a simple and stable process, is easy to operate, and is convenient for industrial production.

[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic flow chart of the preparation method in Example 1 of the present invention;

[0027] Figure 2 is a composite X-ray diffraction diagram of the lead-free ceramic material provided by Examples 1-5 of the present invention,

[0028] in, Figure 2 (a) is the X-ray diffraction pattern of lead-free ceramic material. Figure 2 (b) is the X-ray diffraction pattern at 45-46°;

[0029] Figure 3 It is a schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 1 of the present invention with temperature (-120 to 200° C.);

[0030] Figure 4 Schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 2 of the present invention with temperature (-120 to 200° C.);

[0031] Figure 5 Schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 3 of the present invention with temperature (-120 to 200° C.);

[0032] Figure 6 Schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 4 of the present invention with temperature (-120 to 200° C.);

[0033] Figure 7 Schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 5 of the present invention with temperature (-120 to 200° C.);

[0034] Figure 8 It is a schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 1 of the present invention with temperature (50-350° C.);

[0035] Fig. 9 It is a schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 2 of the present invention with temperature (50-350° C.);

[0036] Fig.10 Schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 3 of the present invention with temperature (50-350° C.);

[0037] Fig.11 Schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 4 of the present invention with temperature (50-350° C.);

[0038] Fig.12 Schematic diagram of the change of the dielectric constant of the lead-free ceramic material provided in Example 5 of the present invention with temperature (50-350° C.);

[0039] Fig.13 is a schematic diagram showing the variation of impedance and phase angle of the lead-free ceramic material provided in Example 1 of the present invention with frequency;

[0040] Fig.14 is a schematic diagram showing the variation of impedance and phase angle of the lead-free ceramic material provided by Example 2 of the present invention with frequency;

[0041] Fig.15is a schematic diagram showing the variation of impedance and phase angle of the lead-free ceramic material provided by Example 3 of the present invention with frequency;

[0042] Fig.16 is a schematic diagram showing the variation of impedance and phase angle of the lead-free ceramic material provided by Example 4 of the present invention with frequency;

[0043] Fig.17 It is a schematic diagram of the change of impedance and phase angle of the lead-free ceramic material provided by Example 5 of the present invention with frequency. DETAILED DESCRIPTION

[0044] A potassium sodium niobate-based lead-free ceramic suitable for high-power devices and a preparation method thereof, wherein the chemical formula of the potassium sodium niobate-based lead-free ceramic is 0.96 (K 0.45 Na 0.55 )NbO3-0.04Bi 0.5+x Na 0.5 ZrO3-0.005CuO, wherein x is the molar percentage of excess Bi element, and x is one of 0, 0.03, 0.05, 0.08 and 0.10. It should be noted that the “-” in the general formula represents a uniform compound formed by multi-component doping.

[0045] The potassium niobate-based lead-free ceramic provided by the present invention has a d 33 308~340pC / N, Q m 107~140, ranked T C The temperature of the piezoelectric ceramic material provided by the present invention is 310-315°C, and the tanδ is 0.011-0.014. It exhibits excellent comprehensive electrical properties, including high piezoelectric constant, high quality factor, high Curie temperature and low dielectric loss, and is suitable for high-power electronic equipment applications. In addition, the piezoelectric ceramic material provided by the present invention does not contain lead elements, and is an environmentally friendly material, which is more beneficial to environmental protection.

[0046] The potassium niobate-based lead-free ceramic provided by the present invention utilizes sodium bismuth zirconate (Bi 0.5 Na 0.5 ZrO3) doping is used to construct a phase structure near room temperature, thereby optimizing the piezoelectric performance. Then, by adding CuO, a large number of defect dipoles are induced to hard-dope the material and improve its quality factor. On this basis, Bi element excess preparation (Bi 0.5+x Na 0.5 ZrO3), using Bi 3+ With K + and Na + The chemical valence difference between the two can adjust the vacancies in the lattice structure, thereby further adjusting its defect structure, thereby synergistically regulating the piezoelectric performance and quality factor while maintaining its high Curie temperature. The Bi element promotes sintering, which can improve the density of the ceramic and reduce its dielectric loss.

[0047] In the potassium niobate-based lead-free ceramic provided by the present invention, the amount of each component must satisfy the chemical formula. When the chemical formula is deviated, the phase structure and domain structure of the obtained lead-free ceramic will change, thereby affecting the piezoelectric performance and Curie temperature. If the molar percentage of all the above components or atomic contents deviates greatly from the ratio, the excess elements are likely to form impurity phases during the doping process, resulting in a decrease in piezoelectric performance.

[0048] The above-mentioned method for preparing potassium sodium niobate-based lead-free ceramics suitable for high-power devices comprises the following steps:

[0049] S101, weighing raw materials of sodium carbonate, potassium carbonate, niobium pentoxide, bismuth oxide, zirconium oxide and copper oxide according to the molar percentage in the chemical formula of potassium niobate-based lead-free ceramics, adding anhydrous ethanol as a ball milling medium to perform rolling ball milling to obtain a mixed powder;

[0050] S102, drying the mixed powder obtained in S101 to obtain a dry and uniformly mixed mixed powder;

[0051] S103, pre-calcining the mixed powder obtained in S102 at 850° C. for 6 hours to obtain dry powder;

[0052] S104, adding a polyvinyl alcohol aqueous solution to the dry powder obtained in S103, and then sequentially performing granulation, pressing and debinding to obtain a ceramic embryo;

[0053] S105. Sinter the ceramic body obtained in S104 at 1080-1100° C. for 5 hours to obtain lead-free ceramics.

[0054] In the present invention, in S101, ball milling is performed in a ball milling jar, the ball milling jar is a nylon jar, and the grinding balls are zirconium balls.

[0055] In the present invention, in S104, 6 wt% to 8 wt% polyvinyl alcohol aqueous solution is added to the dry powder for granulation to obtain powder particles.

[0056] In the present invention, if the added polyvinyl alcohol aqueous solution is less than 6wt%, it is easy to cause the powder particles to be shapeless and it is impossible to obtain a lead-free ceramic material. If it is higher than 8wt%, it is easy to cause the piezoelectric performance to decrease or the powder particles to have holes, resulting in the inability to obtain a dense lead-free ceramic material.

[0057] In the present invention, in S104, the pressing is to press the powder particles in an electric tablet press at a pressure of 15 MPa.

[0058] In the present invention, electrodes are plated on the lead-free ceramic in S105, and voltage is applied for polarization.

[0059] In the present invention, the polarization is to polarize the lead-free ceramic at 3 to 4 kV / cm for 10 to 20 minutes using a withstand voltage tester.

[0060] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0061] Example 1

[0062] In this embodiment, the value of x is 0, and the chemical formula of potassium niobate-based lead-free ceramic is 0.96 (K 0.45 Na 0.55 )NbO3-0.04Bi 0.5 Na 0.5 ZrO3-0.005CuO. In the potassium niobate-based lead-free ceramic provided in this embodiment, Bi 0.5 Na 0.5 ZrO3 is used to construct a phase structure near room temperature, thereby optimizing the piezoelectric performance. The addition of CuO induces a large number of defect dipoles. In this embodiment, the defect structure is regulated by Bi. 3+ With K + and Na + The chemical valence difference between the two can adjust the vacancies in the lattice structure and further adjust its defect structure, thereby synergistically regulating the piezoelectric performance and quality factor while maintaining its high Curie temperature. The Bi element has the effect of promoting sintering, which can improve the lethality of the ceramic and thus reduce its dielectric loss.

[0063] The above-mentioned method for preparing potassium sodium niobate-based lead-free ceramics suitable for high-power devices comprises the following steps:

[0064] S101. According to the molar percentage in the chemical formula of potassium niobate-based lead-free ceramics, weigh analytically pure raw materials of sodium carbonate Na2CO3, potassium carbonate K2CO3, niobium pentoxide Nb2O5, bismuth oxide Bi2O3, zirconium oxide ZrO2 and copper oxide CuO, add ball milling medium anhydrous ethanol in a ball milling jar, and perform rolling ball milling with zirconium balls to obtain a mixed powder.

[0065] S102, drying the mixed powder obtained in S101 to obtain a dry and uniformly mixed mixed powder.

[0066] S103. Pre-calcine the mixed powder obtained in S102 at 850° C. for 6 hours in a corundum crucible to obtain dry powder.

[0067] S104. Add polyvinyl alcohol aqueous solution to the dry powder obtained in S103, and perform granulation, pressing and debinding in sequence to obtain a ceramic body with a diameter of 10 mm and a thickness of 1 mm.

[0068] In S104, 8 wt % polyvinyl alcohol aqueous solution is added to the dry powder and granulated to obtain powder particles.

[0069] In S104, the pressing is to press the powder particles in an electric tablet press, and the mold used has a diameter of 10 mm and a pressure of 15 MPa.

[0070] S105. Sinter the ceramic body obtained in S104 at 1100° C. for 5 hours to obtain lead-free ceramics.

[0071] Silver electrodes are plated on the lead-free ceramic in S105, and voltage is applied in silicone oil for polarization. The lead-free ceramic is polarized at 3-4 kV / cm for 10-20 minutes using a withstand voltage tester. After the polarized lead-free ceramic is left in air for 24 hours, the electrical properties at room temperature and low temperature are tested using IEEE standards.

[0072] Example 2

[0073] In this embodiment, the value of x is 0.03, and the chemical formula of potassium niobate-based lead-free ceramic is 0.96 (K 0.45 Na 0.55 )NbO3-0.04Bi 0.53 Na 0.5 ZrO3-0.005CuO.

[0074] The preparation method of this embodiment is different from that of Embodiment 1 in that the weighed amounts of raw materials in S101 are different, and the rest are the same as the preparation method in Embodiment 1.

[0075] Example 3

[0076] In this embodiment, the value of x is 0.05, and the chemical formula of potassium niobate-based lead-free ceramic is 0.96 (K 0.45 Na 0.55 )NbO3-0.04Bi 0.55 Na 0.5 ZrO3-0.005CuO.

[0077] The preparation method of this embodiment is different from that of embodiment 1 in that the raw material weighing amount in S101 is different, the sintering is performed at 1090° C. for 5 h, and the rest is the same as the preparation method in embodiment 1.

[0078] Example 4

[0079] In this embodiment, the value of x is 0.08, and the chemical formula of potassium niobate-based lead-free ceramic is 0.96 (K0.45 Na 0.55 )NbO3-0.04Bi 0.58 Na 0.5 ZrO3-0.005CuO.

[0080] The preparation method of this embodiment is different from that of embodiment 1 in that the raw material weighing amount in S101 is different, the sintering is performed at 1080° C. for 5 h, and the rest is the same as the preparation method in embodiment 1.

[0081] Example 5

[0082] In this embodiment, the value of x is 0.10, and the chemical formula of potassium niobate-based lead-free ceramic is 0.96 (K 0.45 Na 0.55 )NbO3-0.04Bi 0.60 Na 0.5 ZrO3-0.005CuO.

[0083] The preparation method of this embodiment is different from that of embodiment 1 in that the raw material weighing amount in S101 is different, the sintering is performed at 1080° C. for 5 h, and the rest is the same as the preparation method in embodiment 1.

[0084] Test Example 1

[0085] a. X-ray diffraction experiment

[0086] X-ray diffraction experiments were performed on the potassium sodium niobate-based lead-free ceramics of Examples 1-5, and the obtained X-ray diffraction patterns are as follows: Figure 2 As shown by Figure 2 As can be seen from (a) in the figure, the characteristic peaks between 20 and 70° are:

[100] ,

[110] ,

[002] ,

[200] ,

[210] , and

[211] , respectively, indicating that the ceramic material is a perovskite ceramic. Figure 2 As can be seen from (b), a split peak appears near 45-46°, and the peak intensity ratio deviates from 1:2 or 2:1, indicating that the lead-free ceramic provided by the present invention presents a multi-phase coexistence structure.

[0087] b. Dielectric constant change with temperature test (-150~200℃)

[0088] The potassium sodium niobate-based lead-free ceramics of Examples 1-5 were tested for the change of dielectric constant with temperature. The change of dielectric constant with temperature in the range of -150 to 200°C was tested at a test frequency of 100 kHz. The results are as follows: Figure 3-Figure 7 shown.

[0089] The potassium sodium niobate-based lead-free ceramics provided in Examples 1-5 all exhibit two phase transition peaks, corresponding to the rhombohedral-orthogonal and orthorhombic-tetragonal phase transitions, respectively, and the rhombohedral-orthorhombic phase transition temperature is -60 to -50°C, and the orthorhombic-tetragonal phase transition temperature is 60 to 70°C. Therefore, the orthorhombic-tetragonal phase transition temperature is close to room temperature. Figure 2 It can be clearly seen that potassium sodium niobate-based lead-free ceramics have an orthorhombic-tetragonal two-phase coexistence structure at room temperature.

[0090] c. Dielectric constant change with temperature test (30~500℃)

[0091] The potassium sodium niobate-based lead-free ceramics of Examples 1-5 were tested for the change of dielectric constant with temperature. The change of dielectric constant with temperature in the range of 30 to 500°C was tested at a test frequency of 100 kHz. The results are as follows: Figure 8-Figure 12 shown.

[0092] like Figure 8-Figure 12 As shown, the potassium sodium niobate-based lead-free ceramics provided in Examples 1-5 all present two phase transition peaks, corresponding to the orthorhombic-tetragonal phase transition and the orthorhombic-cubic phase transition, respectively. C , all within the range of 310~315℃.

[0093] d. Impedance and phase angle change test with frequency

[0094] The impedance and phase angle of the potassium sodium niobate-based lead-free ceramics of Examples 1-5 were tested for changes in frequency at room temperature. The results are as follows: Figure 13-Figure 17 shown.

[0095] like Figure 13-Figure 17 As shown, the potassium sodium niobate-based lead-free ceramics provided in Examples 1-5 all exhibited obvious resonant peaks and non-resonant peaks, and the corresponding resonant and non-resonant frequencies were 325-345 kHz and 356-387 kHz, respectively. At the same time, the phase angle of the potassium sodium niobate-based lead-free ceramics was 80-83°.

[0096] e. Electrical test

[0097] Electrical tests were performed on the potassium sodium niobate-based lead-free ceramics of Examples 1-5, and the results are shown in Table 1.

[0098] Table 1. Electrical test data of potassium sodium niobate-based lead-free ceramics of Examples 1-5

[0099]

[0100]

[0101] Therefore, the present invention adopts the above-mentioned potassium sodium niobate-based lead-free ceramic suitable for high-power devices and the preparation method. The potassium sodium niobate-based lead-free ceramic has excellent comprehensive electrical properties, including high piezoelectric constant, high quality factor, high Curie temperature and low dielectric loss, and is suitable for high-power electronic equipment applications.

[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A potassium sodium niobate-based lead-free ceramic suitable for high-power devices, characterized in that: The chemical formula of potassium niobate-based lead-free ceramics is 0.96 (K 0.45 Na 0.55 )NbO3-0.04Bi 0.5+x Na 0.5 ZrO3-0.005CuO, wherein x is one of 0, 0.03, 0.05, 0.08 and 0.

10.

2. The method for preparing a potassium sodium niobate-based lead-free ceramic suitable for high-power devices according to claim 1, characterized in that: The following steps are included: S101, weighing raw materials of sodium carbonate, potassium carbonate, niobium pentoxide, bismuth oxide, zirconium oxide and copper oxide according to the molar percentage in the chemical formula of potassium niobate-based lead-free ceramics, adding anhydrous ethanol as a ball milling medium to perform rolling ball milling to obtain a mixed powder; S102, drying the mixed powder obtained in S101 to obtain a dry and uniformly mixed mixed powder; S103, pre-calcining the mixed powder obtained in S102 at 850° C. for 6 hours to obtain dry powder; S104, adding a polyvinyl alcohol aqueous solution to the dry powder obtained in S103, and then sequentially performing granulation, pressing and debinding to obtain a ceramic embryo; S105. Sinter the ceramic body obtained in S104 at 1080-1100° C. for 5 hours to obtain lead-free ceramics.

3. The method for preparing a potassium sodium niobate-based lead-free ceramic suitable for high-power devices according to claim 2, characterized in that: In S101, ball milling is performed in a ball mill jar, the ball mill jar is a nylon jar, and the grinding balls are zirconium balls.

4. The method for preparing a potassium sodium niobate-based lead-free ceramic suitable for high-power devices according to claim 2, characterized in that: In S103, pre-firing is performed in a corundum crucible.

5. The method for preparing a potassium sodium niobate-based lead-free ceramic suitable for high-power devices according to claim 2, characterized in that: In S104, 6 wt% to 8 wt% polyvinyl alcohol aqueous solution is added to the dry powder and granulated to obtain powder particles.

6. The method for preparing a potassium sodium niobate-based lead-free ceramic suitable for high-power devices according to claim 5, characterized in that: In S104, the pressing step is to press the powder particles in an electric tablet press at a pressure of 15 MPa.

7. The method for preparing a potassium sodium niobate-based lead-free ceramic suitable for high-power devices according to claim 2, characterized in that: Electrodes are plated on the lead-free ceramic in S105 and voltage is applied for polarization.

8. The method for preparing a potassium sodium niobate-based lead-free ceramic suitable for high-power devices according to claim 7, characterized in that: The polarization is performed by polarizing the piezoelectric ceramic body at 3 to 4 kV / cm for 10 to 20 minutes using a withstand voltage tester.

Citation Information

Patent Citations

  • Preparation method of potassium-sodium niobate-based lead-free piezoelectric ceramic

    CN108275999A

  • Potassium-sodium niobate-based leadless piezoelectric ceramic and preparation method thereof

    CN111302797A

  • Lead-free piezoelectric ceramic for medical ultrasonic transducer as well as preparation method and application of lead-free piezoelectric ceramic

    CN112479708A

  • Niobium zirconium acid bismuth potassium sodium copper iron lead-free piezoelectric ceramic with high mechanical quality factor

    CN115572165A

  • Potassium-sodium niobate-based leadless piezoelectric ceramic, preparation method thereof and electronic equipment

    CN117401973A